2003
DOI: 10.1111/j.1365-2133.2003.05600.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical methyl aminolaevulinate photodynamic therapy in patients with basal cell carcinoma prone to complications and poor cosmetic outcome with conventional treatment

Abstract: Topical MAL-PDT is effective in treating BCC at risk of complications and poor cosmetic outcome using conventional therapy. MAL-PDT preserves the skin and shows favourable cosmetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
159
2
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(180 citation statements)
references
References 15 publications
14
159
2
5
Order By: Relevance
“…77 Although MAL-PDT is noninferior to cryotherapy and surgery, the cosmetic advantage associated with MAL-PDT is of great interest for low-risk superficial BCC, because lesions are often multiple, typically affecting skin sites predisposed to dystrophic scarring (such as the trunk). [78][79][80] In randomized trials comparing different treatment modalities for BCC, a recent study demonstrated increased efficacy of imiquimod over MAL-PDT (83.4% versus 72.8%) at 12-month follow-up. This again argues for the advantage of using combination therapies with PDT, namely adding on imiquimod after treatment.…”
Section: Mal-pdt In Treatment Of Bccmentioning
confidence: 99%
“…77 Although MAL-PDT is noninferior to cryotherapy and surgery, the cosmetic advantage associated with MAL-PDT is of great interest for low-risk superficial BCC, because lesions are often multiple, typically affecting skin sites predisposed to dystrophic scarring (such as the trunk). [78][79][80] In randomized trials comparing different treatment modalities for BCC, a recent study demonstrated increased efficacy of imiquimod over MAL-PDT (83.4% versus 72.8%) at 12-month follow-up. This again argues for the advantage of using combination therapies with PDT, namely adding on imiquimod after treatment.…”
Section: Mal-pdt In Treatment Of Bccmentioning
confidence: 99%
“…44 Nos pacientes portadores de CBC superficial e/ou nodular de "difícil tratamento" (lesões extensas, recorrentes, locais de ruim cicatrização ou pacientes portadores de doenças sistê-micas que dificultem a cicatrização), índices de recorrência de 15% a 31% foram observados, após 36 meses de seguimento. 46,47 Para o tratamento dos CBCs com MAL, preconizam-se 2 sessões cm intervalo de 7 dias. Embora as taxas de recorrência sejam maiores, a PDT deve ser considerada uma boa opção frente a situações onde a cirurgia possa ser impeditiva.…”
Section: Aplicações Clínicas Oncológicas Em Dermatologiaunclassified
“…Após seguimento de 48 e 60 meses, a taxa de recorrência foi de 18% e 30%. 46 Sabe-se que MAL pode penetrar até 2 mm no tecido. Assim, os CBCs nodulares mais finos fora de área de risco apresentam os melhores índices de cura.…”
Section: Aplicações Clínicas Oncológicas Em Dermatologiaunclassified
“…For example, in a multicenter, prospectively not controlled study which included patients with recurrent superficial and nodular basal cell lesions, with a risk of complications, with previously poor cosmetic results, it was found that after two PDT sessions carried out in a one week interval the clinical remission at 3 months was 92% for the superficial forms and 87% for the nodular ones. Histological negative margins was obtained in 85% of the superficial basal cell carcinomas and in 75% of the nodular ones (Horn et al, 2003). ALA-PDT can be used as adjuvant therapy in Mohs microsurgery for the BCC after the excision of the tumor.…”
Section: Basal Cell Carcinomamentioning
confidence: 99%